1972
DOI: 10.1530/jrf.0.0290011
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of Luteinizing Hormone in the Blood of Zebu Cattle

Abstract: A solid-phase radioimmunoassay was used to measure lh in the serum of a Zebu cow and heifer during the oestrous cycle. Shortly after the onset of oestrus, serum levels of lh rose sharply to 20 to 120 ng/ml before dropping to baseline levels of about 2 ng/ml after 8 to 10 hr. Elevated lh values were also detected in mid-cycle, although considerable variation in activity over several days occurred with the heifer. Peak values of lh were considerably higher in the serum of the cow than the heifer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…No Razdan & Galhotra, 1980;Arora & Pandey, 1982a; Kanai & Shimizu, 1984;Avenell et al, 1985). Similar values were obtained for zebu by Carr (1972), and for cows by Snook, Saatman, & Hansel (1971); Schams, Schallenberger, Hoffman & Karg (1977) and Dobson (1978a).…”
Section: Pubertysupporting
confidence: 61%
See 1 more Smart Citation
“…No Razdan & Galhotra, 1980;Arora & Pandey, 1982a; Kanai & Shimizu, 1984;Avenell et al, 1985). Similar values were obtained for zebu by Carr (1972), and for cows by Snook, Saatman, & Hansel (1971); Schams, Schallenberger, Hoffman & Karg (1977) and Dobson (1978a).…”
Section: Pubertysupporting
confidence: 61%
“…In cows the increase in LH is a reflec¬ tion of increased frequency of LH pulses which in turn stimulate pulsatile oestradiol production by the ovary . Jain & Pandey (1984) The duration of raised LH values > 10 ng/ml is similar, 6-10 h, in buffaloes (Batra & Pandey, 1982;Avenell et al, 1985), cows (Schams et al, 1977;Dobson, 1978a) and zebu (Carr, 1972).…”
Section: Pubertymentioning
confidence: 83%
“…All serum samples were compared with nih-lh-b6 kindly supplied by the Endocrine Study Section of the National Institutes of Health, Bethesda, Mary¬ land, U.S.A., and a general base-line value of 0-5 to 3 ng/ml was obtained. This value was similar to that obtained during the oestrous cycle (Schams & Karg, 1969a;Carr, 1971). However, it was soon apparent that sharp increases in the level of lh secretion occurred for periods lasting 3 days or less and at varying intervals.…”
supporting
confidence: 89%
“…For studies on the serum lh concentrations of Zebu cattle during the oestrous cycle (Carr, 1971), sequential blood samples were collected from one pregnant cow. A solid phase radioimmunoassay for lh (Goding, Catt, Brown, Kaltenbach, Cumming & Mole, 1969) was carried out on the separated sera and several were found to provide elevated values.…”
mentioning
confidence: 99%
“…Presently available data do not support this expectation. Current information indicates that ovulation in cattle occurs approximately 24 hr after peak LH concentrations (Henricks et al, 1970;Carr, 1972), and that the optimum time for insemination is about 14 hr before ovulation (Sorensen, 1979). Rodeffer et al (1972) also reported that ovulation followed the LH surge by 24 hr in heifers that had been given daily progesterone injections for 9 or 18 days.…”
Section: Syncro-mate-b-treated Heifersmentioning
confidence: 99%